Neonatal complications and neurophysiological development in twins – a long-term follow-up study. (17th January 2022) - Vedel, Cathrine; Larsen, Helle; Holmskov, Anni; Andreasen, Kirsten Riis; Uldbjerg, Niels; Ramb, Jan; Bødker, Birgit; Skibsted, Lillian; Sperling, Lene; Krebs, Lone; Zingenberg, Helle; Laursen, Lone; et al.
Abstract: Objectives: To investigate the association between neonatal complications and neurophysiological development in twins at 18 and 48–60 months of age. Methods: This was a secondary analysis of 841 Danish mono- and dichorionic diamniotic twins from a randomized controlled trial (PREDICT study), which included an assessment of the twin's neurophysiological development using the Ages and Stages Questionnaire (ASQ) that had been filled out by the parents at 18 and 48 or 60 months. The correlation within twin pairs was accounted for by the method of generalized estimating equation. Models were adjusted for maternal educational score and gestational age at delivery. Results: ASQ data were available for 823 children at 18 months and 425 children at 48 or 60 months. Low maternal educational score and preterm delivery <34 weeks were associated with a lower ASQ score at 48–60 months (−15.4 points (95%CI −26.4; −4.5) and −13.2 points (95%CI −23.8; −2.5), respectively). Neonatal sepsis and a compound of intraventricular hemorrhage, retinopathy of prematurity and necrotizing enterocolitis (IVH/ROP/NEC) were associated with lower ASQ score at 18 months (−15.3 points (95%CI −28.1; −2.5) and −30.8 points (95%CI −59.5; −2.1), respectively). Children with IVH/ROP/NEC had a lower ASQ score at 48–60 months (−34.2 points (95%CI −67.9; −0.6)). The associations were not specific to only one ASQ domain. Conclusion: Several neonatal complications are associated with poorer neurophysiological development in twins during childhood, even after adjustment for gestational age at delivery.